A young contracting white dwarf in the peculiar binary HD 49798/RX J0648.0−4418?. Issue 2 (13th November 2017) - Popov, S B; Mereghetti, S; Blinnikov, S I; Kuranov, A G; Yungelson, L R
Abstract: HD 49798/RX J0648.0−4418 is a peculiar X-ray binary with a hot subdwarf (sdO) mass donor. The nature of the accreting compact object is not known, but its spin period P = 13.2 s and P =-2.15 × 10^-15 s s −1 proves that it can be only either a white dwarf or a neutron star. The spin-up has been very stable for more than 20 yr. We demonstrate that the continuous stable spin-up of the compact companion of HD 49798 can be best explained by contraction of a young white dwarf with an age ∼2 Myr. This allows us to interpret all the basic parameters of the system in the framework of an accreting white dwarf. We present examples of binary evolution, which result in such systems. If correct, this is the first direct evidence for a white dwarf contraction in early evolutionary stages.